Efficacy of core stability exercises and short foot exercises in patellofemoral pain syndrome: a brief review - Rajput, Poonam; Mehra, Suman; Yadav, Umesh; Nehra, Kiran; Yadav, Deepak (International Journal of Research in Medical Sciences, 2025)
Patellofemoral pain syndrome (PFPS) is one of the most common knee problems that disturb function and daily activities. Symptoms of PFPS can develop either slowly or abruptly and pain tends to worsen with activities such as squatting, prolonged sitting, stair climbing, jumping or running. Deficits in neuromuscular control of the core muscles and weakness of foot muscles have been associated with occurrence of PFPS. Physical therapy has got a profound role in treatment of patellofemoral pain syndrome patient. Strengthening of the core muscles must have rectified the improper recruitment of the muscles, in order to provide proximal stability, reported that improvement in core muscles could be an effective strategy in the rehabilitation of patients with PFPS. Aim of this review is to find out effect of core stabilization exercises and short foot exercises in patellofemoral pain syndrome. Following electronic databases MEDLINE, PubMed, Cochrane Library and one search engine (google scholar) were searched for literature between 2005 to 2023.